Investigation of the differences between sono-photochemical and photochemical studies for singlet oxygen generation of indium phthalocyanine - Atmaca, Goknur Yasa (ELSEVIER SCIENCE SA, 2021)
One of the most important features of a complex used as a photosensitizer is its capacity of producing singlet oxygen. There is a significant amount of studies for synthesizing effective photosensitizers that generate more singlet oxygen. Unlike other studies, this paper aims to show the differences between photochemical and sono-photochemical studies that contribute to the generation of singlet oxygen. Because the used method is as important as a sensitizer to increase the efficiency of singlet oxygen. For this purpose, new indium phthalocyanine (2) was synthesized and characterized by standard spectroscopy methods; and photophysicochemical properties of compound 2 were investigated. Afterward, the singlet oxygen quantum yield of compound 2 was calculated in both photochemical and sono-photochemical studies and the effects of these studies were compared. The sonophotochemical study (Phi Delta = 0.95) was found to be more effective than the photochemical study (Phi Delta = 0.79). These results show that sono-photochemical study has significantly improved the potential therapeutic effect and the new indium phthalocyanine can be a potential sono-photosensitizer to be used in photodynamic therapy or sono-photodynamic therapy.
Keywords: Photochemical; Phthalocyanines; Singlet oxygen; Sono-photochemical; Chemistry